Association of central blood pressure profile, ambulatory blood pressure parameters with 2D echocardiographic diastolic dysfunction and carotid intima-media thickness in patients with coronary artery disease - Jegavanthan, Arulkumar; Bandara, Lakshman; Jayasekara, Thilina; Sooriyagoda, Hansa; Jeyakanth, Thangarajah (Journal of Cardiovascular Medicine and Cardiology, 2021)
Introduction: Blood Pressure (BP) and its diurnal variability are linked to endothelial dysfunction and arterial stiffness, promoting atherosclerosis which can be observed as intimal thickening in carotid arteries and atherosclerotic lesions in coronary angiograms. Objectives: To evaluate the association of Diastolic Dysfunction (DD) in patients with Coronary Artery Disease (CAD) with central and Ambulatory Blood Pressure Monitoring (ABPM) indices and to assess Carotid Intima Media Thickness (CIMT) in different CAD score groups and then to compare the results with individuals having normal coronaries. Methodology: A descriptive cross-sectional study was conducted at Cardiology Unit Kandy in 2017/18. Patients undergoing elective coronary angiography were categorized in to low, intermediate and high SYNTAX score group. Invasive BP was recorded and Pulsatility Index (PI) was derived. Carotid ultrasound was used to assess CIMT and diastolic function was assessed by 2D echocardiogram. Patients had their 24-hour ABPM recorded. Results were compared with individuals having normal coronary arteries on angiogram. Results: There were a total of 60 subjects out of which 40 (Mean age=59.77±8.73years) had angiographically proven CAD and 20 subjects had no CAD on angiogram. Amongst the CAD group the calculated PI was 0.82±0.36. The ratio of early diastolic mitral inflow velocity to annular velocity (E/e’) which denotes diastolic dysfunction, had strong positive correlation with PI (r=0.942, p=0.002). The mean CIMT for right and left carotid arteries were 0.62±0.11mm and 0.65±0.13mm respectively. A higher but statistically insignificant (p=0.087) CIMT value was noted among patients with SYNTAX score ≥ 23 (7.55±3.01) than in SYNTAX score ≤ 22 (6.87±1.93). Low SYNTAX score group had 45%, (n=18) abnormal dipping pattern in ABPM whereas only 12.5%, (n=05) in the intermediate to high score group showed this pattern, which was statistically highly significant (X2=30.7, p=0.004). Between the CAD group and subjects having normal coronary arteries, the following parameters did not show statistically significant difference. Invasively derived PI (0.76±0.17 and 0.78±0.15, p=0.318), ABPM-derived atherogenic index (r=0.005, p=0.658 and r=0.003, p=0.554), CIMT value (0.63±0.10 mm and 0.52±0.19 mm, p=0.196) and the mitral annular E/e’ velocity (9.56±5.40 and 10.81±3.22, p=0.372). Conclusion: Diastolic dysfunction which is reflected by E/e’ positively correlated with invasively derived PI which indicate incipient arterial stiffness. Therefore E/e’ could be used as a non-invasive tool to assess arterial stiffness indirectly. In ABPM, statistically significant abnormal dipping pattern was observed in low SYNTAX group compared to high group which demonstrates the difference in BP variability and haemodynamic diversity amongst CAD patients with different atherosclerotic disease burden. These findings reflect the usefulness of non-invasive parameters such as E/e’ and CIMT to predict the extent of coronary artery disease and the need for further detailed studies in this field using large patient population in order to find out the best non-invasive parameter which independently predict the CAD burden.